Bringing micro to the macro : adapting clinical interventions for supervision and management - Supranovich, Ruth; Newmyer, Richard (New York, NY : Routledge Books, 2020)
"The field of human services is filled with clinicians turned managers. Many of these managers have not studied business and lack leadership and management experience. Bringing Micro to the Macro: Adapting Clinical Interventions for Supervision and Management shows social workers and other human service professionals how to adapt their clinical and direct practice skills to be effective supervisors and managers. The book demonstrates the parallels between the micro process of client work and the macro process of staff supervision and management. It also shows managers how to properly adapt and employ their micro practice skills to engage, motivate, and guide their staff to achieve maximum impact and productivity. The first four parts are based around the four phases of service delivery in social work: Engagement, Assessment, Intervention, and Evaluation. The book concludes with a part on Self-Care, as this is important if you want to have longevity in this field. Bringing Micro to the Macro is a user-friendly book that can be a tool that new supervisors or managers in social work and human services can reach for when they wonder how to work with staff instead of clients"--
OCLC-licensed vendor bibliographic record.
Keywords: Social work administration; Social workers -- Supervision of; Social case work -- Management; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology / General